130k views
4 votes
-8( -8x -6) = -6x - 22

2 Answers

4 votes
Simplify both sides of the equation, add 6x to both sides, subtract 48 from both sides, then divide both sides by 70. Your answer would be x= -1
User Sacvf
by
7.7k points
6 votes

The answer is x = -1.

First, you use the distributive property and multiply -8 with what's in parentheses on the left side. I'll number the steps below.

1.) -8 times -8x is 64x. Then you take -8 times -6 and get 48.

2.) Now your equation is 64x + 48 = -6x - 22.

3.) Then, you subtract add 6x to the right side, which cancels out the negative, and you add it to the left side getting the equation, 70x + 48 = -22.

4.) Subtract -48 from the left side and add it to the right, getting 70x = -70.

5.) Lastly, you can now divide 70x on the left side, and divide it by 70 on the right and 70 / 70 is equal to 1.

So X = -1.

I hope that was helpful!

User AishApp
by
7.4k points